Desain Constructed Wetland sebagai Pengolahan Tersier untuk Menyisihkan Mikroplastik - Viviani, Amalia; Nur, Ansiha; Sri Komala, Puti (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
This study aims to plan the design of a constructed wetland as a tertiary treatment to remove microplastics in wastewater so that it is safe to discharge into water bodies or the environment. The design site is the Anaerobic Upflow Filter (AUF) type wastewater treatment plant in Jambi City. The design uses the Sub Surface Flow Constructed Wetland (SSFCW) system and the Horizontal Sub Surface Flow (HSSF) system with the selected plants being Phragmites communis. The planned design is 1 unit for a treatment capacity of 24 m3/day, which is located downstream of each AUF type WWTP in Jambi City. The constructed wetland design refers to the design criteria and design calculations contained in Book A, a guide for the calculation of fecal sludge treatment buildings. This study also calculates the Bill of Quantity (BOQ), which is determined based on the dimensions of the design drawing, and the Resource Allocation Plan (RAB), which is determined based on the amount of work multiplied by the Analysis of the Unit Price of Work (AHSP). AHSP refers to the Jambi Governor Regulation No. 1 of 2024 on Unit Price Standards. Based on the research results, it was found that the dimensions of the constructed wetland design were 64 m × 16 m × 0.9 m, so the estimated cost for the construction of the design was IDR 405,415,773.84 with an estimated microplastics removal efficiency of 100%.